(3TQM GdJUQjas - (3GdJaJGRGfj, SYO GdOjf, SYhO Hf YeQ Hf YHO Gddg, J (B793 (3g`s ((3CHh GdbGSe Hf NOGhQOjs)
(3ChdgG (B:s
(3HSe Gddg (B... (3deG QCjJ GdeNJUQ GdPj Ufag GdGeGe GdaGVd GdcGed bOhI GdeMbbjf YR edI hGdOjf YHO GdhgGH Hf EHQGgje GdRfLGfj QMeg Gddg JYGdi eNJUQG GfWhi Ydi Ydi eHGMK TQjaI (B...s
(3BNQgG (B:s
... (3bGd GdeUfa aj TQM GdgGOj GdeQGO HGdfhY GdMGdI GdJj YdjgG GdaGYd Jbhd gh MSf GdQcHI Zf cGf QchHg MSfG jYfj Ef Pdc deG cGf ehLhOG efg (B...(3hcPdc GdHhGbj hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\219s
(3cTa GdXfhf (B2\1139s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas